Using Media in the Form of Favorite Movies to Teach Grammar and Vocabulary to Eleventh graders - Annisa Emillia Tri Rhovaidah; Muhamad Sofian Hadi; Mutiarani Mutiarani (Universitas Cokroaminoto Palopo, 2021)
The results of learning English for students in class XI high school are poor, particularly in terms of vocabulary and grammar. It is necessary to have learning media that is expected to improve the results of English learning in order to improve the learning process that has been going on so far. The goal of this study is to see if there is an increase in words and a focus on grammar in XI grade high school students' favorite film media. The author uses media in the form of favorite movie watching to see if there is an effect of favorite movie watching on improving vocabulary and grammar in English. The treatment is carried out by the author in accordance with the theory he has discovered. Because Class XI high school students have an interest in the media of watching favorite movies, Using Media by Watching Favorite Movies was chosen as a method of improving words and grammar. Following the researcher's treatment, it was discovered that giving the Favorite English film to class XI high school students had a significant impact on their ability to increase vocabulary and focus on grammar.